Management of Dental extraction in patients received multiple therapy of antiplatelet - Dr. Hani M. Khlaif (Scientific Trends, 2022)
Antiplatelet therapy involves giving antiplatelet drugs to patients to prevent thrombosis, either prophylactically or in patients undergoing percutaneous coronary intervention. This study examined the effectiveness of a tooth extraction approach in dual antiplatelet patients.
Keywords: Dental extraction, antiplatelet, management epinephrine